(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s
(3ChdgG (B:s
(3CNHQfG CHh GdNjQ YGUe Hf GdMSf Hf eMeO Ydj YGUe (B... (3fPQJ CNJj Cf JML MGajI ZjQ efJYdI, aCJjJ QShd Gddg Udi Gddg Ydjg hSde aPcQJ Pdc dgs
(3BNQgG (B:s
(3Yf QLd Yf GdfNYj Yf cejd Hf RjGO GdfNYj (B... (3dG Mhd hdG bhI EdG HGddg hdG edLG hdG efLG ef Gddg EdG Edjg cfR ef cfhQ GdLfI(B. (3BNQ GdLRA GdKGdKs
(3QhGjI CHj YeQ YHO GdhGMO Hf eMeO Hf YHO Gddg Hf egOj GdaGQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs